ANALISIS KENYAMANAN MANUSIA (HUMAN COMFORT) PADA SISTEM PENDINGIN DESICCANT CAIR TENAGA MATAHARI MENGGUNAKAN KONFIGURASI ALIRAN BERLAWANAN (COUNTER FLOW) - R. Hengki Rahmanto (Jurnal Konversi Energi dan Manufaktur, 2015)
High water vapour content in air can cause a number of problems as for human or surrounding materials. For human a high water vapour can create physiological stress, discomfort, and also can encourage ill health. While, the cause for the environment is can accelerate the corrosion of metals, accelerate the growth of spores and mould, can reduce the electrical resistance of insulators and etc. Desiccant systems have been proposed as energy saving alternatives to vapor compression air conditioning for handling especially the latent load and also sensible load. Use of liquid desiccants offers several design and performance advantages over solid desiccants, especially when solar energy is used for regeneration. The liquid desiccants contact the gas inside the packed tower of liquid desiccant solar cooling system and the heat transfer and mass transfer will occur. This paper is trying to study the human comfort analysis inside the packed tower of dehumidifier systems. This human comfort analysis consist of human comfort and energy that consume by the system. The results of this paper later on can be used to determine the best performance of the systems.